Elevated Risk of Venous Thromboembolism in People Living with HIV - Zhang, Quan; Peng, Fei; Li, Meizhi; Yi, Qiong; Tang, Wei; Wu, Shangjie (Viruses, 2022)
Human immunodeficiency virus (HIV) has been generally considered as a highly adaptive and rapidly evolving virus. It still constitutes a major public health problem all over the world despite an effective outcome in the prevention and reversal of the development and prognosis by using antiretroviral therapy. The salient question lies in the more frequent emergence of a series of comorbidities along with the prolongation of the life, which deeply affects the survival in such group. Venous thromboembolism (VTE) has been recognized to be the third most common cardiovascular condition within people living with HIV (PWH). In terms of its mechanism of action, the occurrence of VTE is quite multifactorial and complex in HIV. Prior exploration concerning the etiology of VTE in PWH identifies general, disease-specific, and miscellaneous factors for explaining its occurrence and development. VTE has constituted an important role in PWH and may increase its all-cause mortality. Therefore, it is quite necessary to understand VTE from the following aspects of epidemiology, pathophysiology, molecular mechanisms, and therapeutic interventions so as to balance the risks and benefits of anticoagulation and optimize corresponding treatment.